Early detection of lung cancer risk using data mining - Ahmed, Kawsar; Kawsar, Abdullah-Al-; Kawsar, Emran; Emran, Abdullah-Al-; Jesmin, Tasnuba; Mukti, Roushney Fatima; Rahman, Md. Zamilur; Ahmed, Farzana (© 2013 Asian Pacific Journal of Cancer Prevention, 2016)
This article was published in the Asian Pacific Journal of Cancer Prevention [© 2013 Asian Pacific Journal of Cancer Prevention] and the definite version is available at : http://dx.doi.org10.7314/APJCP.2013.14.1.595 The Journal's website is at:http://koreascience.or.kr/article/ArticleFullRecord.jsp?cn=POCPA9_2013_v14n1_595